Eliminating ‘Thick’ Borders: Analysing the Legal Framework on Non-Tariff Barriers in the Africa Continental Free Trade Area Agreement (Strathmore Law Review, 2021)
African countries have long recognised that regional integration is vital if Africa is to optimise its growth potential and boost its bargaining power in the global marketplace. This explains the proliferation of several Regional Trade Agreements (RTAs) across the continent culminating in the conclusion of the landmark African Continental Free Trade Area (AfCFTA). However, despite the concerted efforts to boost intra-trade among African countries, African borders remain ‘thick’ because of the continued existence of Non-Tariff Barriers (NTBs) that reverse gains made from initiatives of trade liberalisation. Accordingly, if the landmark Africa Continental Free Trade Area (AfCFTA) is to be successful, it must strive to address and eliminate Africa’s NTBs. It is argued in this paper that while the AfCFTA makes some important strides in reducing NTBs in intra-African trade, there are still some significant gaps in the AfCFTA’s provisions on NTBs that need to be addressed. Some of these gaps include: the lack of a comprehensive legal framework that adequately addresses all the categories of NTBs and the lack of clear guidelines on how to promote harmonisation among conflicting measures among RTAs. This article singles out and analyses provisions on NTBs under the AfCFTA with the aim of determining whether the AfCFTA addresses the challenges currently facing other RTAs in tackling NTBs. The author will identify shortcomings in the legal framework of the AfCFTA with the aim of making proposals to address them.